2019
DOI: 10.3390/min9040240
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Mixing Intensity on Rheological Properties of Cemented Paste Backfill

Abstract: Cemented paste backfill (CPB) consists of a mixture of fine particles, mainly consisting of tailings and cement dispersed in water. Therefore, it is necessary to introduce an intensive shearing force into the paste during mixing in order to maintain an equilibrium between agglomeration and dispersion. It is influential for the macroscopical fluidity and rheological properties when changes occur in the microstructure of CPB under shear. However, the research on how mixing affects the properties of CPB is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The weakening effect of SWP on the UCS and elastic modulus are consistent with the findings reported by Hou et al (2020). In addition, the mechanical properties of CTB are related to its internal microstructure (Yang et al, 2019;Zhou et al, 2019;Tana et al, 2021); the results indicated that the seepage would cause a certain degree of damage to the internal microstructure of CTB.…”
Section: Effect Of Seepage On Mechanical Properties Of Ctbsupporting
confidence: 85%
“…The weakening effect of SWP on the UCS and elastic modulus are consistent with the findings reported by Hou et al (2020). In addition, the mechanical properties of CTB are related to its internal microstructure (Yang et al, 2019;Zhou et al, 2019;Tana et al, 2021); the results indicated that the seepage would cause a certain degree of damage to the internal microstructure of CTB.…”
Section: Effect Of Seepage On Mechanical Properties Of Ctbsupporting
confidence: 85%
“…The spread test of filling slurry adopts a metal frustum with a top diameter of 36 mm, a bottom diameter of 60 mm and a height of 60 mm (Chen et al, 2020;Li W et al, 2020), as shown in Figure 6. R/S SST rheometer was used to test the rheological parameters of filling slurry (Yang et al, 2019;Cheng et al, 2020;Kou et al, 2020), as shown in Figure 7.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…Before the experimental analysis, the mills tailings were placed in a drying box furnace and naturally cooled to prepare the paste tailings samples. Particle size distribution (PSD) of the tailings specimens was determined (Figure 1) using the size analysis and determination of soil constants procedure (ASTM D421) [20] and Malvern top sizer laser particle size analyzer (Shanghai, China) [21]. Many paste tailings were used wet in order to conduct a set of experimental tests needed for material characterization.…”
Section: Tailings Characteristics Based On Elements Collected Through Jinchuan Nickel Mine Sitementioning
confidence: 99%